Criminal Law Protection for Demonstrators from Repressive Actions by Authorities - Samuji; Andi Wahyuddin Nur; Zulkarnain S; Yulianis Safrinadiya Rahman; Nopiana Mozin (Universitas Muhammadiyah Palu, 2025)
Demonstrations represent a tangible form of freedom of expression and opinion, which are fundamental elements of a democratic system. In Indonesia, this right is constitutionally guaranteed and further regulated under Law No. 9 of 1998 concerning the Freedom to Express Opinions in Public. However, in practice, the implementation of this right often clashes with repressive actions by security forces. The excessive use of force, unlawful arrests, and acts of violence against protesters illustrate the weak legal protection afforded to citizens exercising their constitutional rights. Such circumstances raise serious concerns regarding the enforcement of human rights and the rule of law in Indonesia. This article aims to analyze the criminal law protection afforded to demonstrators from repressive actions by law enforcement officers who exceed their authority. The discussion examines the national legal framework, the principles of criminal liability for officers, and mechanisms for fair and proportional law enforcement. The study adopts a normative juridical approach, analyzing statutory regulations, legal doctrines, and relevant case studies. The findings indicate that repressive acts by officers may constitute criminal offenses when they violate the principles of legality and proportionality in the use of force. Furthermore, the state bears a constitutional obligation to provide effective legal protection for citizens who become victims of such abuses of power. Therefore, a stronger system of accountability and oversight is essential to ensure that citizens’ rights to peaceful assembly and expression are genuinely protected within Indonesia’s legal framework.